Pengaruh Inflasi Dan Pertumbuhan Ekonomi Terhadap Tingkat Kemiskinan Di Kota Palembang - Novera Wandira; Maya Panorama (Medina-te : Jurnal Studi Islam, 2021)
In ieconomic itheory, ieconomic igrowth ihas ian iinfluence ion ipoverty ilevels, ibut ithe iresults iof ithe ianalysis iof ithis istudy iindicate ithat ieconomic igrowth ihas ino ieffect ion ipoverty ilevels ibased ion i2016-2020 iresearch idata iobtained ifrom ithe iRoadmap ifor istrengthening ithe iPalembang iCity iRegional iInnovation iSystem iin i2018-2023. iThis istudy iaims ito idetermine iand ianalyze ithe ieffect iof iinflation iand ieconomic igrowth ion ipoverty ilevels iin iIndonesia. iThe iresearch imethod iused iis idescriptive iquantitative iusing isecondary idata iand ithe idata ianalysis imethod iis ilinear iregression ianalysis, icorrelation ianalysis, idetermination ianalysis, iand ihypothesis itesting. iThe iresult iof ithe iresearch ishows ithat iinflation ihas ian ieffect ion ithe ilevel iof ipoverty ibecause ithe ivalue iof itcount i> ittable i, ibut ieconomic igrowth idoes inot ihave ia isignificant ieffect ion ithe ilevel iof ipoverty ibecause ithe ivalue iof itcount i< ittable i. iSimultaneously, iInflation iand iEconomic iGrowth ihave ia isignificant ieffect ion ithe iPoverty iLevel, iwhich iis iindicated iby ithe ivalue iof iFcount i> iFtable.